The relationship between performance evaluation systems and motivation: A case study from three NGOs in Egypt. - Aloush, Heba (AUC Knowledge Fountain, 2016)
The main objective of this research is to measure the relationship between Performance Evaluation System (PES) in the NGO sector in Egypt and the employees’ motivational level. Additionally, the research will explore the employees’ perceptions of the PES in the NGO sector in Egypt. The study was conducted over three NGOs; CARE International, Save the Children, and the Misr El Kheir. Both qualitative and quantitative methods have been used to answer the main research question and to evaluate the PES in the three organizations in addition to the evaluation of the motivators and the PES challenges from the employees’ perspectives. The study uses questionnaires and semi-structured interviews as data collection tools. A total of 133 respondents participated in the questionnaire and 12 employees were interviewed to comment on various aspects of the PES process. The study adopted Herzberg motivational theory and Maslow hierarchy of needs theory to examine the relationship between PES and motivation. The research came up with a number of findings. The most prominent one is the importance of the intrinsic factors in motivating the employees as well as the importance of activating a rewarding system that is related to the PES outcomes. Also, it was noted there are prerequisites for effective PES which if exist, the PES will be more effective. For example the multi rater technique is one of those prerequisite that can increase the objectivity of the PES process. III Employees have different challenges with the PES implementation like lacking knowledge of the evaluation system, struggling with the ambiguity of the rating scale or the evaluation form itself. Keywords: PES, Motivation, Challenges, Motivators and 360 degree appraisal